Strategy for Implementing Blockchain Technology in Higher Education Administrative Management - Ali Mufron; Meicsy E.I Najoan; Bekti Utomo (International Journal of Educational Narratives, 2024)
Background. Higher education institutions are faced with demands to increase efficiency and security in administrative management, including management of student data, certification, transcripts, and others. With the many changes in student administration data and the importance of security and transparency in the administration process, blockchain technology has become a concern in providing innovative solutions in this regard. Purpose. This research aims to analyze the potential and benefits of implementing blockchain technology in higher education administrative management with a focus on security, efficiency and transparency. Method. Research Method: The research method used includes a literature study regarding information technology and higher education management, as well as a comprehensive analysis of blockchain implementation in managing student administrative data.    Results. The research results show that the implementation of blockchain technology in higher education administrative management can increase data security and transparency, reduce administrative costs, speed up the certification verification process, and enable the development of a more efficient administrative management system. Conclusion. In conclusion, this research confirms that blockchain technology has great potential to change the management paradigm of higher education administration by providing better data security, increasing process efficiency, and creating a more transparent and decentralized administrative environment. Thus, the implementation of blockchain technology in higher education administrative management can provide significant benefits in facing the complex challenges faced by these educational institutions.